Voltammetry in the presence of ultrasound: The limit of acoustic streaming induced diffusion layer thinning and the effect of solvent viscosity - Marken, F; Akkermans, R; Compton, R (1996)
Fundamental aspects and applications of power ultrasound in electrochemistry are presently in rapid development. However, from the many literature reports using various types of, sometimes not very well characterized, sonoelectrochemical reactor, only a fragmented, often contradictory picture of the associated physicochemical processes arises. In this study, a classification of different sonoelectrochemical cell types depending on the effect of insonation is given and experimental results for 'face-on', 'side-on', and sonotrode geometries are compared. In particular, a minimum decrease in the diffusion layer thinning or a maximum increase in the transport-limited current can respectively be observed as the ultrasound power is increased. The comparative mass transport characteristics and the effect of solvent viscosity allow turbulent acoustic streaming to be identified as a major physical process which governs the mass transport in undivided sonoelectrochemical cells employing an immersion horn transducer. The effect of solvent viscosity on the limit of diffusion layer thinning is investigated using the electrochemical reduction of tetracyanoquinodimethane dissolved in dichloromethane, acetonitrile, dimethylformamide, and dimethylsulfoxide. A reciprocal relationship between the kinematic viscosity v and the limiting value for the diffusion layer thickness δlim is observed.